THE EFFECTIVENESS OF PASSIVE EXERCISES ON ARTERIAL BLOOD GASES IN MECHANICALLY VENTILATED SUBJECTS FROM INTENSIVE CARE UNITS - Delia-Claudia STAN; Iosif SANDOR (Cluj University Press, 2022)
Introduction: Mechanically ventilated critically ill subjects are often given strict bed rest and sometimes completely immobilized because of the severity of their illness and the administration of drugs such as sedatives. Active mobilization is not possible in subjects under deep sedation and unable to follow commands. In this scenario, passive therapy is an interesting alternative. Objective: This study aimed to evaluate the effectiveness of passive exercises on arterial blood gases in mechanically ventilated subjects from intensive care units. Methods: Five mechanically ventilated subjects participated in the study. The subjects were assigned to one study group, which received passive exercises for one daily session, including ten repetitions in three series per articulation. Arterial Blood Gases were assessed by arterial blood sample analysis with the Stat Profile Prime Plus device. Results: The results revealed a marked improvement in arterial blood gas exchange as compared to baseline reflecting an increase in FIO2- the inspiratory fraction of oxygen, pO2- partial pressure of oxygen, and pO2/FIO2- the ratio between the partial pressure of oxygen and the inspiratory fraction of oxygen and a decrease in CO2- carbon dioxide. Conclusions: The passive exercise showed a slight trend of beneficial changes at the cellular level in mechanically ventilated subjects since the first day after admission, which may indicate a reduction in the inspiratory fraction of oxygen and at the end, extubation of subjects.